Profil Pasien Trauma akibat Kecelakaan Lalu Lintas yang Dirawat di Instalasi Rawat Darurat Bedah RSUP Prof. Dr. R. D. Kandou Manado Periode 1 Januari â€“ 31 Desember 2017 - Zai, Petrina C.; Wagiu, Angelica; Rawung, Rangga (e-CliniC, 2018)
Abstract: Traffic related death and trauma are major health problems in developing countries. Traffic accident needs multidisciplinary approach. Data regarding the profile of traumatic patients due to traffic accidents are still limited especially in Indonesia. This study was aimed to obtain the profile of traumatic patients due to traffic accidents admitted to the emergency unit of Surgery Department, Prof. Dr. R. D. Kandou Hospital Manado, from 1st January to 31st December 2017. This was a descriptive retrospective study using medical record data of the patients. Samples were all traumatic patients due to traffic accidents admitted to the emergency unit of Surgical Department. The results showed that of 173 patients the majority were as follows: adults 121 patients (69.9%), males 123 patients (71.1%), drivers 113 patients (65.3%), bikers 138 patients (88.5%), without using safety equipment 93 patients (59.6%), negative alcohol 141 patients (81.5%), head trauma 91 patients (52.6%), and outpatients as many as 130 patients (75.1%).Keywords: trauma, traffic accidentÂ Abstrak: Trauma dan kematian akibat kecelakaan lalu lintas (KLL) merupakan masalah kesehatan masyarakat yang utama di negara berkembang. Kecelakaan lalu lintas memerlukan penanganan dengan pendekatan multidisipliner. Data tentang profil pasien trauma akibat KLL terbilang masih sedikit khususnya di Indonesia. Penelitian ini bertujuan untuk mengetahui profil pasien trauma akibat KLL yang dirawat di Instalasi Rawat Darurat Bedah RSUP Prof. Dr. R. D. Kandou Manado periode 1 Januari s/d 31 Desember 2017. Jenis penelitian ialah deskriptif retrospektif menggunkan data rekam medik pasien. Sampel penelitian ialah semua pasien trauma akibat KLL yang dirawat di Instalasi Rawat Darurat Bedah RSUP Prof. Dr. R. D. Kandou Manado. Hasil penelitian menunjukkan bahwa dari 173 pasien KLL, didapatkan yang terbanyak ialah pasien usia dewasa 121 orang (69,9%), jenis kelamin laki-laki 123 orang (71,1%), pengendara 113 orang (65,3%), pengguna motor 138 orang (88,5%), tidak memakai alat pengaman 93 orang (59,6%), negatif alkohol 141 orang (81,5%), trauma kepala 91 orang (52,6%), dan rawat jalan 130 orang (75,1%).Kata kunci: trauma, kecelakaan lalu lintas